Design consideration of a low-voltage low-power transimpedance amplifier - Zhong, Hua. (2010)
As complementary metal-oxide-semiconductor (CMOS) technology continues to scale down, impact of deep submicron noise over the reliability of computation becomes significant. The Probabilistic CMOS (PCMOS) theory provides a nice model for such phenomenon. Based on this theory, the concept of a truly random number generator (TRNG) making use of a PCMOS inverter is proposed. The system is referred to as random event source integrated noise amplifier (RESINA), whose primary application is in cryptography. In this final year project (FYP), the RESINA system is investigated. The author managed to develop the specifications of the RESINA amplifier according to the understanding of the PCMOS theory as well as the thermal noise model. A new modeling method of the input thermal noise is also proposed, and the existing designs of the RESINA amplifiers are evaluated accordingly. Simulation results of individual component as well as the integrated system are presented and analyzed in this project. Potential improvements of the RESINA design are also suggested and detailed in this report.